Costa Rica : First and Second Reviews Under the Extended Arrangement Under the Extended Fund Facility, Request for Extension of the Arrangement, and Rephasing of Purchases-Press Release; Staff Report; and Statement by the Executive Director for Costa Rica. (IMF Staff Country Reports; Country Report ;, 2022)
On March 1, 2021, the IMF Executive Board approved a 36-month arrangement under the Extended Fund Facility (EFF) with access of SDR 1.23749 billion (335 percent of quota, equivalent to USD 1.778 billion) to support the country's response to the pandemic and its reform efforts toward strong, inclusive, and sustainable growth. The authorities' proactive response to the COVID-19 crisis, combined with sustained export performance, have supported a robust recovery. The outlook remains subject to downside risks, amid tighter global financial conditions, higher commodity prices, and the threat of new COVID variants.